A primer on optimal policy projections - Thomas Dengler; Rafael Gerke; Sebastian Giesen; Daniel Kienzler; Joost Röttger; Alexander Scheer; Johannes Wacks (Deutsche Bundesbank, 2024)
Optimal policy projections (OPPs) offer a flexible way to derive scenario-based policy recommendations. This note describes how to calculate OPPs for a simple textbook New Keynesian model and provides illustrations for various examples. It also demonstrates the versatility of the approach by showing OPP results for simulations conducted using a medium-scale DSGE model and a New Keynesian model with heterogeneous households.
Keywords: C63; E20; E31; E47; E52; E58; 330; Optimal monetary policy; macroeconomic projections; New Keynesian models; household heterogeneity